Wordstar 200 plus ([Carmel], 1988)
Contents: moving the cursor and removing text; copying a file turing off justify, turing on display, spacing and printing; opening headers, footers and footnoes a format.
Keywords: Wordstar (file máy tính),WordStar (Computer file),Word processing